Hygiene and Clean Water Sanitation Problems Post Flood Disaster in Medan Selayang District - Syifa, Assyifa Deswita Mrp; Susilawati, Susilawati; Nadia, Nadia Amanda Azwa; Tria, Tria Syafira Matondang; Dinda, Dinda Agus Tantri; Hairum, Hairum Nafsiah Purba; Boangmanalu, Lilis Karlina (Universitas Ibn Khaldun Bogor, 2025)
Floods are natural disasters that often hit Indonesia, having a significant impact on public health and environmental quality. This study aims to evaluate the state of clean water and sanitation after the flood in Medan Selayang District. The results of the study showed that 73.33% of the water became dirty, dirty, and cloudy after flooding, which was caused bypollutionfrommud, garbage, and house hold waste. Poorsanitation, including direct discharge of sewage intorivers by 60% of people, worsens the situation and increases the risk of water-based diseases such as diarrhoea and skin infections, especially among children who are the most vulnerable group. In addition, 56.6% of homes experience damp and odour conditions, which contribute to discomfort and health risks. This study emphasizes the need for infrastructure assistance and restoration programs that focus on improving sanitation and access to clean water to prevent further post-disaster health impacts.